The impact of transportation planning on agricultural areas and plant health: a case study of Antalya/Konyaaltı West Ring Road - Engin Kepenek; Ersin Aksoy; Şerife Betül Çetinkaya (TeMA: Journal of Land Use, Mobility and Environment)
It is stated in the literature that changes in land cover/land use may have positive or negative effects on accessibility and rural-urban distinction in the region. Similarly, increasing accessibility in an area may lead to unplanned urbanization, traffic congestion, air and noise pollution, and a decrease in environmental quality of life due to the impact on land use, and most importantly, destruction of agricultural areas. In the planning of urban and rural areas, the interaction with each other and the formal separation of rural and urban areas are important, and many analyses such as accessibility, protection of agricultural areas, building density and population should be carefully made in order to avoid negative impacts on each other. In the studies carried out without such analyses, unplanned or unjustified urban areas emerge where the direction of urban development has not been determined. In this study, the West Ring Road in the Konyaaltı district (Antalya), where a similar situation is experienced, and the surrounding agricultural areas are analyzed. It is claimed that the agricultural lands around the West Ring Road have lost their agricultural quality. With this study, we seek empirical answers to these claims. Our aim is to analyze the effects of the West Ring Road on the agricultural areas around it, in conjunction with plant health, through GIS (Geographic Information System) and Remote Sensing methods. As a result of the study, the plant health in the rural agricultural areas on the periphery of the West Ring Road was not negatively affected.